Pesticide Emissions from Soil – Fate and Predictability. (1st February 2013) - Ashworth, Daniel; Luo, Lifang; Yates, Scott
The need to safeguard global food supply has led to an increasing use of chemical pesticides during the last 60 Years. However, this need should be balanced with our responsibility also to safeguard human and environmental health. By definition, chemical pesticides are toxic compounds and can become pollutants of soil, water and air after their application. Such pollution can lead to human risk pathways, e.g. by the presence of pesticide residues in the food we eat, the water we drink, and the air we breathe. Once applied to the surface or subsurface of a soil, the fate of a pesticide compound is governed by its decomposition/degradation, its adsorption onto the solid phase of the soil, its dissolution in the liquid phase with subsequent movement by leaching, and its volatilization to the gas phase with subsequent diffusion through soil pores and/or emission to the atmosphere. Together with environmental variables (e.g. temperature, soil type and structure, soil moisture content), the physical and chemical properties of individual pesticides dictate the extent to which each of these processes acts upon a given compound. The potential for air contamination depends on the extent to which the pesticide converts to the gaseous state, i.e. its volatility. For some pesticides (e.g. the class known as fumigants), almost 100% of the chemical mass is potentially volatile under field conditions. In such a scenario, the potential for emissions from soil, and therefore air contamination, is very high. Research to understand the processes controlling pesticide emissions better can lead to the development of strategies that reduce these emissions; thereby assisting farmers in the protection of air quality and compliance with increasingly stringent air quality regulations. This article describes the extent of pesticide emissions from soil, the environmental and human health concerns of these emissions, and the efforts being made to predict these emissions using model simulations.